Case study on inventory management of Cancorp Inc. - Dy, Glady G.; Enderez, Anatolio V. (Diliman, Quezon City College of Engineering, 2003)
Cancorp, Inc. was established around February 2001, by Rowell Can Corporation with a contract with Nestle Philippines to be its sole provider of tin cans for their powdered milk products. This one-on-one business partnership provides Cancorp with objectives based solely on Nestle's requirements. This is difficult in the business perspective since, if Nestle becomes dissatisfied with Cancorp's performance, it would switch to another supplier and Cancorp will lose its business. The Powdered milk industries are slowly gearing towards an all-tin can packaging primarily because of the unfriendly effects of aluminum foil packaging to the environment. This trend provides Cancorp with a projected continuously increasing demand in the future, given that Nestle Philippines is the country's largest producer of powdered milk. Cancorp has two warehouses. Although the warehouses are separate entities, the dynamics of each warehouse is a function of the other warehouse. This is an important observation worthy of elaboration since it is inappropriate to study a particular inventory system if the demands for its goods, which dictates the movement of its level, is dependent on some factor. Given the company's information, the group was able to determine inventory problems from the 2 warehouses of Cancorp, Inc. These are: (1) The inventory turnover rate for both warehouses are very low because most items in the inventory stays in the warehouse for unnecessarily long periods of time. (2) Ordering is done very frequently but the ordered products are not actually going to be used up immediately, only to be added to an already very high level of stock. For the inventory management system on Cabuyao Warehouse, the group recommends the company to use lower on hand inventory. Having seasonality on the data, the group calculated different reorder points for both peak and off-peak periods. For the peak periods, the group recommends to lower the company's on hand inventory from its current of 300,00 cans to 150,000 cans. This resulted to an increase inventory turnover rate from 13.613% to 21.603%. For the off-peak periods, it is lowered from its current of 300,000 to 210,000 cans with an increase inventory turnover rate from 5.774% to 7.308%. Lowering the on hand inventory for both peak and off-peak period also reduced the overall total cost. Moving to the Pasig Warehouse of Cancorp, Inc., the group proposed the company to use an MRP Software (Material Requirements Planning) in order to come up with a feasible and optimizing system in the Pasig warehouse. It has been established that the demand for cans in Pasig warehouse is dependent on the consumption of cans in the Cabuyao warehouse. Because of this, the group resorted to Material Requirement Planning. MRP serves as a minimizing inventory tool because it allocates production time and schedules production itself after considering when the finished goods are actually needed. The purpose of the MRP system to Pasig warehouse, is to track and monitor the inventory level of the Cabuyao warehouse and, using the Nestle's rolling forecast, determine the finished goods requirements of the Cabuyao Warehouse. The main objective of this software is to ensure that all finished goods are delivered to Cabuyao as soon as possible, that is, immediately after production. This way, the inventory level of the Pasig warehouse shall be highly minimized. All of the recommendations are aligned with the comparative priorities of Cancorp, Inc., Which are on-time delivery and production flexibility.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Cancorpo Incorporated; Container industry; Production engineering